Development Trend of Cooling Technology for Turbine Blades at Super-High Temperature of above 2000 K - Liang Xu; Zineng Sun; Qicheng Ruan; Lei Xi; Jianmin Gao; Yunlong Li (Energies, 2023)
Aeroengines and heavy-duty gas turbines are the core power equipment in the field of national defense and energy. Their research and development (R&D) level and manufacturing level represent the status of a country’s heavy industry in the world. The common cooling technologies of turbine blades including impingement cooling, film cooling, effusion cooling, layer cooling, pin fin cooling, and rough ribs were introduced in this paper. With the continuous improvement of the efficiency and performance of aeroengines and gas turbines, the turbine inlet temperature increases gradually every year; turbine blades will be exposed to higher gas temperatures in the future as gas temperatures break 2000 K. In order to ensure the safe operation of turbine blades under severe super-high temperature working conditions, cooling technology must be developed emphatically. This paper first reviews the research status of turbine blade cooling technology and points out future research focuses. The development trends of next-generation turbine blade cooling technology for above 2000 K temperature are summarized from several aspects: the innovative excavation of high-efficiency composite cooling configuration, multi-objective cooperative cooling structure and optimization design based on 3D printing, composite cooling structure design and optimization based on an artificial intelligence algorithm, tapping the cooling potential of new cooling media and heat pipes, integrated thermal protection with new thermal insulators, and the application of low-resistance and high-efficiency surface dimple cooling. The summary of this paper can provide a reference for the researchers of turbine blade cooling technology.